Gender transformative socio-technical innovation Bundling for resilience, empowerment, productivity, and food security in Makueni County, Kenya - Nchanji, Eileen; Njiru, Emerita; Ketema, Dessalegn; Lutomia, Cosmas Kweyu (2025)
The Alliance of Bioversity International and CIAT through CGIAR Program on Scaling for Impact, in collaboration with KALRO, Gender Equality and Social Inclusion Accelerator, and county governments is convening a series of county-level workshops to reach farmer groups and wards not previously covered in the pilot phase of socio technical innovation bundling. The workshops aim to promote joint reflection on locally adapted GTSTIBs, socialize stakeholders and new partners on GTSTIBs, and co-create roadmaps to institutionalize inclusive innovation models at scale, beyond the maize and common bean value chains.